2011
DOI: 10.1016/j.foodhyd.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Improved heat stability by whey protein–surfactant interaction

Abstract: 2One of the main changes that occur during heat treatment of milk is whey protein denaturation, 3 which in its turn may lead to protein aggregation and gelation. In this contribution, the effect of 4 lysophospholipids, the main components of lysolecithins, as well as alternative surfactants, on 5 heat-induced whey protein aggregation has been studied. Hereby, attention was paid to the 6 relation between polar lipid molecular structure (e.g. effect of alkyl chain length, effect of polar 7 head group) and heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Though interactions between WP and surfactants may occur at room temperature, they can only be obviously observed during thermal treatment (Le et al, 2011). Thermal gelation properties of WP in the presence of soybean lecithin were monitored by an oscillation rheology and results were shown in Figure 5A.…”
Section: Oscillation Rheological Properties Of Wp or Pwp In The Presementioning
confidence: 99%
“…Though interactions between WP and surfactants may occur at room temperature, they can only be obviously observed during thermal treatment (Le et al, 2011). Thermal gelation properties of WP in the presence of soybean lecithin were monitored by an oscillation rheology and results were shown in Figure 5A.…”
Section: Oscillation Rheological Properties Of Wp or Pwp In The Presementioning
confidence: 99%
“…The increase in the aggregate size with the addition of these emulsifiers was not expected and is in contrast to observations reported before. Several studies observed a reduction in aggregate size when non-ionic emulsifiers were added to the protein before heating. , Hansted et al proposed the formation of emulsifier micelles with or around BLG and, thus, a solubilization of the protein, making it more difficult for the molecules to approach each other. However, there were differences regarding the systems used within the published studies and in this present work.…”
Section: Resultsmentioning
confidence: 99%
“…Whey proteins are milk proteins (mainly β-lactoglobulin and α-lactalbumin) that are widely used in food design due to a variety of functionalities, including: water binding, gelation, emulsification, and foaming [ 77 ]. In food processing, whey proteins are usually denatured due to heat treatments and thereby they aggregate, either in self-aggregation or with other food particles [ 78 , 79 ]. Through extensive research, it has been shown that the interactions between whey proteins and small molecules can change their molecular structures and the physico-chemical properties [ 79 ], supporting their applications in food.…”
Section: Proteins In Milkmentioning
confidence: 99%
“…In food processing, whey proteins are usually denatured due to heat treatments and thereby they aggregate, either in self-aggregation or with other food particles [ 78 , 79 ]. Through extensive research, it has been shown that the interactions between whey proteins and small molecules can change their molecular structures and the physico-chemical properties [ 79 ], supporting their applications in food.…”
Section: Proteins In Milkmentioning
confidence: 99%